A generalized life-cycle cost model for rail transit: making decisions between at-grade mode and underground mode. Issue 1 (2nd January 2016) - Wang, Xingju; Zhang, Zhanmin; Chen, Jinjie; Han, Zhe
Abstract: The life-cycle cost of a rail transit system is critical to decision makers when choosing the appropriate mode, e.g., at-grade versus underground, to build a rail transit system over the past decades in China. This is particularly true when private sectors are involved through alternative delivery methods such as public-private partnerships (PPPs). This article proposes a generalized life-cycle model that considers various attributes of rail transit systems common to big cities in China. Line 1 of Shijiazhuang rail transit was employed as a case study to validate the model, where the life-cycle costs of at-grade and underground mode were analysed using both traditional methods mode and the proposed methodology. The analysis results show that, in terms of the generalized life-cycle cost, the underground mode is preferred over the at-grade mode, which is consistent with the current practices of rail transit construction in China.